Chapter 3: Whakapaparanga: Social Structure, Leadership and Whāngai - Kawharu, Merata; Newman, Erica (Te kōparapara: an introduction to the Māori world, 2018)
Keywords: hapū; hapū politics; history; iwi; rangatiratanga; social conditions; social life and customs; whanau

Chapter 5: Where to next? Decolonisation and the stories in the land: Imagining Decolonisation - Jackson, Moana (Imagining Decolonisation, 2020)
Keywords: colonisation; decolonisation; hapū politics; iwi politics; rangatiritanga; tikanga | indigenous law

Rights and Sovereignty of Indigenous Peoples: Implications for Foreign Policy - Bargh, Maria (Public Participation in Foreign Policy, 2012)
The predominant forms of foreign policy discussed these days are underpinned by an assumption of Crown sovereignty in Aotearoa New Zealand. However, the first diplomatic relations and foreign policy in this country were conducted by hapū and iwi Māori.1 Prior to the 1800s, Māori had a long history of interaction in the Pacific and with other nations. Such interactions were governed by specific legal and political practices and institutions. A number of the concepts upon which these practices and institutions were based included whakapapa (genealogy), utu (balance), mana (respect) and koha (reciprocity).2
Keywords: diplomacy; foreign policy; free trade agreement; hapū politics; human rights; international relations; iwi politics; te ao Māori